Social perception in children and adolescents with ADHD: The role of higher-order cognitive skills. (April 2023) - Cardillo, Ramona; Crisci, Giulia; Seregni, Stefano; Mammarella, Irene C.
Abstract: Despite children with ADHD frequently experiencing difficulties in social perception, the mechanisms underlying this impairment have been poorly explored. In this study, we examined social perception in children with ADHD, comparing them with typically-developing (TD) children on semi-naturalistic tasks, and considering the effect of nonverbal signal recognition. Our aim was to ascertain whether the two groups' social perception related to different types of stimulus (video, audio or combined/multimodal). The role of three higher-order cognitive skills (theory of mind, attention and pragmatic language) was also investigated. Thirty-six children with ADHD, and 36 TD controls were tested. Social perception was significantly associated with participants' ability to recognize nonverbal signals, and with the stimulus presentation modality. Children with ADHD only performed less well than TD children with combined stimuli. As concerns the higher-order cognitive skills, theory of mind had a significant role in both groups, but only with the video and combined stimuli, while attention explained most of the variance in social perception for all types of stimulus. Better pragmatic language skills were only associated with a better social perception in TD children, whatever the type of stimulus presented. Semi-naturalistic tasks should be included when assessing social perception in ADHD, and both theory of mind and attention should be the object of efforts to enhance social perception in the ADHD population. Highlights: Emotion recognition was tested in ADHD and typical groups by considering different stimulus conditions. The role of higher-order cognitive skills and nonverbal signals was considered. Nonverbal signals and stimulus conditions influenced emotion recognition. ADHD children performed worse only in the condition close to real-life interactions. Socio-emotional abilities and attention were related to emotion recognition in ADHD.